2008
DOI: 10.1016/j.ejpain.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

What do different databases tell about the use of opioids in seven European countries in 2002?

Abstract: Caution is required when interpreting the data on opioid consumption between countries because of differences in the collection and reporting of data. Better recording of opioid consumption is needed for meaningful analysis of opioid consumption and its possible effect on pain management in different countries. Data on opioids consumed for cancer-related pain in comparison with chronic non-malignant pain are needed. A uniform method of collection of data on analgesic consumption should be established for all E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 7 publications
5
60
2
1
Order By: Relevance
“…These represent an estimate of the precision of the equianalgesic ratio employed in the calculations, and show if conclusions would change if different equianalgesic ratios were used. As reported by Hamunen et al, 5 the estimates based on DDD indicate that Sweden had the highest and Finland the lowest total opioid consumption. However, when using OMEQ, the opioid consumption in Denmark was higher compared with Sweden, even if the maximum or minimum equianalgesic ratios were employed in the calculation.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…These represent an estimate of the precision of the equianalgesic ratio employed in the calculations, and show if conclusions would change if different equianalgesic ratios were used. As reported by Hamunen et al, 5 the estimates based on DDD indicate that Sweden had the highest and Finland the lowest total opioid consumption. However, when using OMEQ, the opioid consumption in Denmark was higher compared with Sweden, even if the maximum or minimum equianalgesic ratios were employed in the calculation.…”
Section: Resultssupporting
confidence: 51%
“…The observation by Hamunen et al 5 that Sweden had the highest total opioids consumption per capita measured in DDD was unexpected, and did not comply with previous literature that showed that Denmark had the highest opioid consumption. 13 The overall aim of the present study was to explore whether opioid consumption data were interpreted differently using OMEQ or DDD as the unit of measurement.…”
Section: Introductioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The other opioid analgesic identified in this study was morphine, which showed a high falsification ratio in Spain, although official utilization in the same country was low, as underlined in international reports [45]. Even though less accessibility to strong opioids in participating countries might explain why opioid analgesics are not the most frequently reported diverted drugs [45], by contrast with observations in the USA [46,47,48], the most recent data indicate an increasing use of opioid analgesics in all European countries [44,49] and an increasing trend in diversion [3,15]. The need to limit the consequences of potential abuse of these substances (and the subsequent limitations) should not affect their access for pain management.…”
Section: Discussionmentioning
confidence: 62%
“…In European countries, the rate of opiate consumption ranges from 2.6 to 21 per 1,000 adult inhabitants [12,13,14,15]. In Iran, opium and its derivatives are the most common abusive drugs.…”
Section: Introductionmentioning
confidence: 99%